Investigation on Effect of Some Operating Conditions on Flow and Heat Transfer of Supercritical Co2 In Helical Coiled Tubes Via Multilevel Factorial Methodology - D., Devandran; A. N., Oumer; N. T., Rao; F., Basrawi; Hassan, Ibrahim (UniKL, 2017)
In order to optimize the thermal-hydraulic performance of supercritical carbon dioxide (scCO2) flowing through helically coiled tubes, the main and interaction effects of two operating parameters such as inlet pressure, and inlet mass flow rate on the Nusselt number and friction factor was investigated by applying a multilevel factorial design (MFD) analysis. The developed model is intended to analyze the friction factor (f) and Nusselt number (Nu) of heating process using scCO2 as a working fluid using two-factor and three-level MFD method. Three different inlet pressures (8.00 MPa, 9.03 MPa and 10.05 MPa) with three different inlet mass fluxes (0.0131 m3/s, 0.0151 m3/s and 0.0167 m3/s) at constant inlet temperature of 27 °C are considered. It was observed from the simulation results that inlet pressure has no significant effect on the Nusselt number while varying the mass flow rate affected the Nu significantly. On the other hand, increments of both inlet pressure and mass flux have decreased the friction factor. The MFD studies showed that for the Nusselt number, mass flow rate was found to be the most significant factor followed by the pressure in terms of importance. However, in case of friction factor, inlet pressure was the most significant factor. In general, it is proved from this study that a multilevel-factorial design was an effective method for determining the influences of inlet pressure and mass flow rate on the thermal-hydraulic performance of scCO2 heating process.